"Without being able to read, what's literacy mean to them?": Situated beliefs about literacy for students with significant disabilities. (October 2017) - Ruppar, Andrea L.
Abstract: Beliefs about students and pedagogical knowledge have been identified as key barriers to accessible general education content and contexts for students with significant disabilities. In this case study of a high school special education literacy class, I examine definitions of literacy, expectations about students, and self-efficacy in the process of teaching literacy to students with significant disabilities. Team members expressed disjointed understandings about the purpose of literacy, lacked pedagogical knowledge, and had poor self-efficacy. Beliefs about "high" and "low" students, defined by students' orality, affected team members' perceptions about the feasibility and priority of literacy for various groups of students. Highlights: Decisions about literacy are influenced by assumptions about students' potential. In special education settings, teachers sort students based on orality. Assumptions about potential are based on students' orality and behavior. Low teacher self-efficacy leads to limited literacy opportunities.